2017
DOI: 10.15561/18189172.2017.0508
|View full text |Cite
|
Sign up to set email alerts
|

Special aspects of hemo-dynamic and reaction of erythrocytes in blood to standard physical load of different qualification female volleyball players

Abstract: Purpose:to study the aspects of organism's cardio-hemo-dynamic and blood erythrocytes reaction of female volleyball players to standard physical load. Material:with functional methods we studied cardio-hemo-dynamic and with the help of scanning electronic microscopy -erythrocytes' structure in 18 female volleyball players of different qualification (age -22.0±0.60 years). Results:it was found that maximal physical load causes substantial changes in cardio-hemo-dynamic, which depend on female volleyball players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Earlier works by Popel 'et al, [2,3] have shown that athletes after competitions have an accumulation of acidic metabolites in peripheral blood, especially lactate. In this case, the shift of the pH towards the acid reaction (up to 7.26) occurs due to the activation of the synthesis of 2,3-DFG.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Earlier works by Popel 'et al, [2,3] have shown that athletes after competitions have an accumulation of acidic metabolites in peripheral blood, especially lactate. In this case, the shift of the pH towards the acid reaction (up to 7.26) occurs due to the activation of the synthesis of 2,3-DFG.…”
Section: Discussionmentioning
confidence: 94%
“…In a number of studies [2,3,11] it was shown that when practicing strength sports, special requirements are made to the functional reserves of the athlete's cardio-respiratory system. This immediately affects the functional state of the peripheral circulation and is often associated with the level of erythrocyte hemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations